Public choice: A survey - Charles B. Blankart (Center for Economic Studies and ifo Institute (CESifo), 2013)
Public Choice is the merger between political science and economics. In the introductory sections of this survey it is investigated what we can expect from the logic of public choice. How far is it able to produce consistent results? Is public choice consistent with liberty? What can be done to reconcile these core principles? In the later, more applied sections, several forms of democracies in unitary and federal states are investigated. The dynamics of public choice are considered in the theory of the political business cycle. The survey ends with some thoughts on public choice in the euro crisis.
Keywords: B25; D72; H20; 330; Public Choice; Theorie